Kemungkinan penggunaan teknologi pelapisan permukaan dengan ultraviolet dan berkas elektronik indonesia - Nurhajati, Dwi Wahini (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1992)
Ultraviolet (UV) or electron beam (EB) curing coating technology is the crosslingking polymerization of a coating materials on a substrate ( such as paper, metal, wood or plastic) via interaction with incident UV/EB irradiation, and this technology has been commercial used in a number of countries. The coating materials are monomer, oligomer or a mixture of monomer and oligomer. The crosslink polymer coated surface has been know to be resistant to water, organic solvent and heat. This paper gives an overview of the coating technology by ultraviolet or electron beam irradiation, and their applicability in Indonesia. INTISARI Teknologi pelapisan permukaan dengan ultraviolet (UV) atau berkas elektron (EB) merupakan proses polimerisasi ikat silang dari bahan pelapis secara langsung di atas substrat (misal kertas, kayu, logam maupun plastik) melalui insiden iradiasi sinar ultraviolet ataupun berkas eletron, dan teknologi ini sudah banyak digunakan dalam monomer, oligomer atau campuran keduanya. Permukaan yang telah dilapisi dengan polimer ikat saling dikenal tahan terhadap air, pelarut organik dan juga panas. Makalah ini akan memberikan gambaran tentang kemungkinan pengunaan teknologi pelapisan permukaan dengan iradiasi ultraviolet ataupun elektron di Indonesia.